Diagnostic accuracy of plasma kynurenine/tryptophan ratio, measured by enzyme-linked immunosorbent assay, for pulmonary tuberculosis. (October 2020) - Adu-Gyamfi, Clement Gascua; Snyman, Tracy; Makhathini, Lillian; Otwombe, Kennedy; Darboe, Fatoumatta; Penn-Nicholson, Adam; Fisher, Michelle; Savulescu, Dana; Hoffmann, Christopher; Chaisson, Richard; Martinson, Neil; Scriba, Thomas Jens; et al.
Highlights: Despite the availability of several TB diagnostics, there is an urgent need for a non-sputum-based test capable of detecting active TB. Plasma kynurenine/tryptophan ratio can be measured using an ELISA method. Plasma kynurenine/tryptophan ratio is a sensitive plasma-based diagnostic biomarker for active TB. Abstract: Introduction: The World Health Organization has identified the need for a non-sputum-based test capable of detecting active tuberculosis (TB) as a priority. The plasma kynurenine-to-tryptophan (K/T) ratio, largely mediated by activity of the enzyme indoleamine 2, 3-dioxygenase, may have potential as a suitable biomarker for active TB. Method: We evaluated a commercial enzyme-linked immunosorbent assay (ELISA) in comparison to mass spectrometry for measuring the K/T ratio. We also used ELISA to determine the K/T ratio in plasma from patients with active TB compared to latently infected controls, with and without HIV. Results: The two methods showed good agreement, with a mean bias of 0.01 (limit of agreement from −0.06 to 0.10). Using ELISA, it was found that HIV-infected patients with active TB disease had higher K/T ratios than those without TB (median, 0.101 [interquartile range (IQR), 0.091–0.140] versus 0.061 [IQR, 0.034–0.077], P  < 0.0001). At a cutoff of 0.080, the K/T ratio produced a sensitivity of 90%, a specificity of 80%, a positive predictive value (PPV) of 82%, and a negative predictive value (NPV) of 90%. In a receiver operating characteristics analysis, the K/T ratio had an area under the curve of 0.93. HIV-uninfected patients with active TB also had higher K/T ratios than those with latent TB infections (median, 0.064 [IQR, 0.040–0.088] versus 0.022 [IQR, 0.016–0.027], P  < 0.0001). A cutoff of 0.040 gave a sensitivity of 85%, a specificity of 92%, a PPV of 91%, and an NPV of 84%. Conclusion: The plasma K/T ratio is a sensitive biomarker for active TB. The K/T ratio can be measured from blood using ELISA. The K/T ratio should be evaluated as an initial test for TB.